Efficacy and Tolerability of a Fixed-Dose Combination of Rosuvastatin and Ezetimibe Compared with a Fixed-Dose Combination of Simvastatin and Ezetimibe in Brazilian Patients with Primary Hypercholesterolemia or Mixed Dyslipidemia: A Multicenter, Randomized Trial - Antonio Carlos Amedeo Vattimo, MD, MSc; Francisco Antonio Helfestein Fonseca, MD, PhD; Douglas Costa Morais, BSc; Larissa Fontes Generoso, PhD; Renata Herrera, BSc; Cristiane Moraes Barbosa, BSc; Maria Cristina de Oliveira Izar, MD, PhD; Rita Antonelli Cardoso, PhD; Stevin Zung, MD, PhD (Elsevier, 2020)
ABSTRACT: Background: The addition of ezetimibe to statin therapy has been reported to result in increased efficacy for reduction of LDL-C levels and achievement of lipid targets, compared with monotherapy.Objective: This study was designed to demonstrate the noninferiority of therapy with fixed-dose rosuvastatin plus ezetimibe formulations versus fixed dose simvastatin and ezetimibe formulations for reduction of LDL-C levels in Brazilian patients with hypercholesterolemia or mixed dyslipidemia.Methods: Phase III, multicenter, randomized, parallel, open-label, noninferiority study that included male and female participants (aged 21-80 years) with hypercholesterolemia or mixed dyslipidemia. After a 1-week screening period with washout of lipid-lowering medications when needed, patients were treated with simvastatin 20 mg/d for 5 weeks. Participants with LDL-C levels ≥100 mg/dL after the initial treatment were submitted to a 1-week washout period, and then randomized 1:1 to receive either combined rosuvastatin 10 mg + ezetimibe 10 mg (R/E) or simvastatin 20 mg + ezetimibe 10 mg (S/E) for 4 weeks and, if they still did not achieve the stipulated target, doses were readjusted to rosuvastatin 20 mg + ezetimibe 10 mg or simvastatin 40 mg + ezetimibe 10 mg, respectively, for 4 weeks.Results: One hundred twenty-nine participants were enrolled, including 66 in R/E and 63 in S/E. At the end of simvastatin 20 mg treatment period, mean LDL-C values were 124.79 mg/dL and 121.27 mg/dL for participants randomized to R/E and S/E arms, respectively. After 4 weeks of R/E 10 mg + 10 mg or S/E 20 mg + 10 mg combined treatments, adjusted mean LDL-C values were 74.21 mg/dL and 85.58 mg/dL, respectively (P = 0.0005), and after 9 weeks, with dose adjustment to R/E 20 mg + 10 mg in 6 patients and to S/E 40 mg +10 mg in 19 patients, LDL-C adjusted mean values were 75.29 mg/dL and 86.62 mg/dL, respectively (P = 0.0006). There was a statistically significant difference between the association R/E and S/E (P = 0.0013) in percentage change of LDL-C after 9 weeks of combined treatments. The adjusted mean difference was estimated at -10.32% (95% CI, -16.94% to -3.70%). The LDL-C <100 mg/dL target was achieved in a significantly greater proportion of participants at week 4 in the R/E compared with the S/E arm (84.8% vs 68.2%; P = .0257), and at week 9, the proportion was 81.2% versus 73.0%, respectively (P = 0.23). LDLC <70 mg/dL was achieved at a significantly greater proportion in the R/E arm, both at week 4 (45.4% vs 15.9%; P = 0.003) and week 9 (40.9% vs 15.9%; P = 0.0017). A statistically significant difference at week 9 (P = 0.0106) was observed in fasting blood glucose in the R/E arm, but the overall incidence of adverse events was not significantly different between groups.Conclusions: Rosuvastatin and ezetimibe fixed dose combination in both 10 mg/10 mg and 20 mg/10 mg doses, respectively, provided significantly lower levels of LDL-C compared with simvastatin and ezetimibe in doses of 20 mg/10 mg and 40 mg/10 mg, respectively. The fixed-dose combinations were both effective and well tolerated in this Brazilian study population. ClinicalTrials.gov identifier: NCT01420549. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)